2021
DOI: 10.1159/000516464
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib for Severe COVID-19-Related Hyperinflammation in Nonresponders to Steroids

Abstract: <b><i>Introduction:</i></b> Currently, severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection is a major public health problem worldwide. Although most patients present a mild infection, effective strategies are required for patients who develop the severe disease. Anti-inflammatory treatment with JAK inhibitors has been considered in SARS-CoV-2. <b><i>Methods:</i></b> In this study, we presented our experience in a group of severe SARS-CoV-2 Chilea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…( Ikeda et al, 2022 ) Coincidentally, RUX and other JAK inhibitors have been shown to be effective for treating severe COVID-19 infections, potentially as a result of the anti-inflammatory effects of these drugs. ( Sarmiento et al, 2021 )…”
Section: Discussionmentioning
confidence: 99%
“…( Ikeda et al, 2022 ) Coincidentally, RUX and other JAK inhibitors have been shown to be effective for treating severe COVID-19 infections, potentially as a result of the anti-inflammatory effects of these drugs. ( Sarmiento et al, 2021 )…”
Section: Discussionmentioning
confidence: 99%
“…In recent study of 18 COVID-19 patients, ruxolitinib was successfully used to treat the hyperinflammatory state in 55% of the patients, regardless of prior steroid or tocilizumab therapy. However, a few patients exhibited severe evolution despite ruxolitinib therapy [113].…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 99%
“…Moreover, in the interpretation of IL-6, the dual effect as proinflammatory as well as anti-inflammatory cytokine has to be considered. In hyperinflammation in COVID-19, proinflammatory effects are assumed to be mediated via soluble IL-6 receptors (30)(31)(32). Thus, a decrease of IL-6 in the hyperinflammatory phase is desirable.…”
Section: Discussionmentioning
confidence: 99%